Retracted: Redox‐dependent regulation of hepatocyte absent in melanoma 2 inflammasome activation in sterile liver injury in mice. Issue 1 (29th November 2016) - Sun, Qian; Loughran, Patricia; Shapiro, Richard; Shrivastava, Indira H.; Antoine, Daniel J.; Li, Tunliang; Yan, Zhengzheng; Fan, Jie; Billiar, Timothy R.; Scott, Melanie J.
Abstract : Sterile liver inflammation, such as liver ischemia‐reperfusion, hemorrhagic shock after trauma, and drug‐induced liver injury, is initiated and regulated by endogenous mediators including DNA and reactive oxygen species. Here, we identify a mechanism for redox‐mediated regulation of absent in melanoma 2 (AIM2) inflammasome activation in hepatocytes after redox stress in mice, which occurs through interaction with cytosolic high mobility group box 1 (HMGB1). We show that in liver during hemorrhagic shock in mice and in hepatocytes after hypoxia with reoxygenation, cytosolic HMGB1 associates with AIM2 and is required for activation of caspase‐1 in response to cytosolic DNA. Activation of caspase‐1 through AIM2 leads to subsequent hepatoprotective responses such as autophagy. HMGB1 binds to AIM2 at a non‐DNA‐binding site on the hematopoietic interferon‐inducible nuclear antigen domain of AIM2 to facilitate inflammasome and caspase‐1 activation in hepatocytes. Furthermore, binding of HMGB1 to AIM2 is stronger with fully reduced all‐thiol HMGB1 than with partially oxidized disulfide‐HMGB1, and binding strength corresponds to caspase‐1 activation. These data suggest that HMGB1 redox status regulates AIM2 inflammasome activation. Conclusion : These findings suggest a novel and important mechanism for regulation of AIM2 inflammasome activation in hepatocytes during redox stress and may suggest broader implications for how this and other inflammasomes are activated and how their activation is regulated during cell stress, as well as the mechanisms of inflammasome regulation in nonimmune cell types. (Hepatology 2017;65:253‐268).